The Role of Parents from Various Backgrounds Toward Online Learning In Elementary School Due to The Covid-19 Pandemic At Sidoarjo - Zuhrotunisa Eviana Indah Kumala; Ahmad Misbahul Munir; Bakhrul Huda (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Kediri, 2022)
The purpose of this research was to identify how the implementation model of online learning is conducted by children aged 8-10 years in Sidoarjo and how the role of their parents with different backgrounds in online learning. The research method used was qualitative research with a case study. Data collection techniques in this study used interviews and documentation. For data analysis, there were two stages utilized, namely data reduction, and data presentation. The findings of this study showed that the implementation of online learning was by utilizing the WhatsApp application because it is considered to be more universal and straightforward. Thus, children aged 8 to 10 years old in Sidoarjo could learn online. In addition, Google Classroom was employed for exercises or exams. While the involvement of parents from several backgrounds in online learning was highlighted to be quite similar, such as (1) assisting children in learning and doing assignments, (2) supervising children in using cell phones, (3) explaining the material if they did not understood, (4) providing learning facilities such as cellphones or internet quotas, and (5) affording motivation or support.